2019
DOI: 10.1021/acs.energyfuels.9b01621
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Spontaneous Imbibition of CO2-Rich Brine in Tight Oil Reservoirs

Abstract: This paper focuses on the CO 2 -EOR in fractured tight oil reservoirs after water-flooding treatment. In previous works, few studies were presented about the spontaneous imbibition experiments of CO 2 -rich brine at formation pressure. We investigated the influence of CO 2 injection on spontaneous imbibition, which is an essential mechanism to improve oil recovery in tight reservoir. In this paper, a laboratory equipment was set up to conduct spontaneous imbibition experiments at formation temperature of 65 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…By comparing the numerically simulated results obtained in this study with the existing experimental and simulation data, it can be concluded that the variations of imbibition recovery and imbibition rate under the influences of rock wettability, oil–water viscosity ratio, interfacial tension, and microfractures have the same trend as the previous studies, , which further extend the broad scope of application of the method.…”
Section: Numerical Results and Discussionsupporting
confidence: 69%
“…By comparing the numerically simulated results obtained in this study with the existing experimental and simulation data, it can be concluded that the variations of imbibition recovery and imbibition rate under the influences of rock wettability, oil–water viscosity ratio, interfacial tension, and microfractures have the same trend as the previous studies, , which further extend the broad scope of application of the method.…”
Section: Numerical Results and Discussionsupporting
confidence: 69%
“…Researchers subsequently conducted extensive experiments to assess the impact of matrix and fluid characteristics on spontaneous imbibition. These characteristics include porosity, permeability, viscosity, interfacial tension (IFT), wettability, mineral composition, fluid chemical composition, boundary conditions, and salinity [9][10][11][12][13][14][15][16]. These studies have led to continuous enhancements in the models of spontaneous imbibition.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation performed by Wang et al explored the influence by surfactants on the imbibition process in tight reservoirs. The results demonstrate that altering the capacity of a surface to be wetted and reducing the force between two interfaces can improve the extraction of fluids by capillary action in low-permeability reservoirs. Khosravi performed an experiment to investigate the capacity of ionic surfactants to be assimilated by the surfaces of rocks and evaluated their influence on imbibition recovery. The findings indicate that the absorption efficiency of the active agent on the rock surface is primarily influenced by electrostatic interactions, leading to an enhancement in imbibition recovery. Sun et al conducted a mathematical model to examine the impact for interfacial tension on imbibition.…”
Section: Introductionmentioning
confidence: 99%